The Effect of Implementing Interactive Learning Media Based on Virtual Laboratory on Student Learning Outcomes in Force Topic - Naki, Nadrah Pratiwi; Abdjul, Tirtawaty; Nurhayati, Nurhayati; Odja, Abdul Haris; Yusuf, Muhammad; Payu, Citron S. (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Learning media is a teaching aid that educators can use to convey lesson material, increase student creativity, and increase student attention during the learning process. This research examines the effect of implementing interactive learning media based on virtual laboratory on student learning outcomes in force topic at SMP Negeri 1 Gorontalo. This research uses an experimental method, and the research design used is a group pre-test and post-test design. The subjects of this research were 30 students in each class divided into three classes: experimental class, replication 1, and replication 2. The data analysis techniques used are normality, hypothesis, and n-gain tests. The results of the hypothesis testing criteria were T-count ≥ T-table with a level of ∝ = 0.05 for the experimental class, replication 1, and replication 2; therefore, Ho is rejected, and Ha is accepted. This is also supported by the acquisition of the course average normalized gain for all sample classes, both experimental and replication classes, which fall into the high and medium categories in the experimental class (0.71), replication 1 (0.70), and replication 2 (0.66). Data analysis shows that the average post-test score for the experimental and replication classes is higher than the pre-test. This indicates that virtual laboratory media improves student learning outcomes in force topics. This research concludes that using interactive learning media based on virtual laboratories can be an effective alternative for improving the quality of science learning in schools.